Elements of interior design - Otis, Jon.; Insight Media (Firm). (New York distributed by Insight Media, 2007)
Examines how the element of space adds a new level to visual design theory.
Producer, James Strzelinski.
DVD
Keywords: Interior decoration; Architecture -- 21st century; Video discs